(untitled) (Research, Society and Development, 2023)
The arboviruses transmitted by the female Aedes aegypti are considered a public health problem and the vector control is essential to reduce the spread of disease-causing pathogens. The main objective of this research was to investigate the chemical composition of the Streptomyces hygroscopicus biomass extract and its larvicidal capabilities against the Aedes aegypti mosquito. Regarding the result of the prospection of the chemical composition of the extract, based on the qualitative colorimetric methodology of the presence of secondary metabolites, there was a positive indication for the alkaloid test and a negative one for flavonoids. Through Gas Chromatography coupled to mass spectrometry it was possible to infer the presence of 9-12-octadecadienoic acid followed by the presence of 9-12-octadecadienoic acid and linoleic acid. The larvicidal activity against Ae. aegypti (LC50) of the extract diluted with 1% DMSO was 155.4 ppm, the highest mortality was with 250ppm reaching 100 porcent. Finally, it was seen that the oily extract of S. hygroscopicus biomass was able to act on Ae. aegypti, showing as a potential larvicidal for this species.